Climate cosmopolitics and the possibilities for urban planning - Houston, D.; MacCallum, Diana; Steele, W.; Byrne, J. (2016)
Cosmopolitical action in a climate-changed city represents different knowledges and practices that may seem disconnected but constellate to frame stories and spaces of a climate-just city. The question this article asks is: how might we as planners identify and develop counter-hegemonic praxes that enable us to re-imagine our experience of, and responses to, climate change? To explore this question, we draw on Isabelle Stengers's (2010) idea of cosmopolitics-where diverse stories, perspectives, experiences, and practices can connect to create the foundation for new strategic possibilities. Our article is empirically informed by conversations with actors from three Australian cities (Sydney, Brisbane, and Perth) who are mobilizing different approaches to this ideal in various grassroots actions on climate change.